(untitled) (Advances in Military Technology, 2022)
The aim of this paper is to acquaint the readers with civilian application of energetic materials, i.e. solid propellants when they are practically applied in different civilian spheres. These are successfully used for dynamic tests of different types of structures, or in those cases when they are used against the hailstorms damaging from time to time the agricultural products, which have to be replaced from other outer sources, as well as it is necessary to compensate the agricultural producers financial losses.